Delay of late-venous phase cortical vein filling in acute ischemic stroke patients: Associations with collateral status. Issue 2 (February 2017) - Bhaskar, Sonu; Bivard, Andrew; Parsons, Mark; Nilsson, Michael; Attia, John R; Stanwell, Peter; Levi, Christopher
Evaluation of the venous system may be useful in stroke prognostication and patient selection for acute intervention strategies. We report a novel phenomenon, delayed-late venous phase cortical vein filling, observed on dynamic computed tomography angiography obtained using multidetector computed tomography scanner, in acute ischemic stroke patients. The aim of this study was to examine the frequency of delayed-late venous phase cortical vein filling and assess its association to baseline collateral status. Dynamic computed tomography angiography images of acute ischemic stroke patients, being assessed for reperfusion therapy, were prospectively studied. Delayed-late venous phase cortical vein filling was defined by late venous phase opacification of cortical veins despite contrast clearance from contralateral cortical veins on dynamic computed tomography angiography. Time to peak of maximum arterial enhancement was recorded. A total of 117 patients (mean age = 70.6 ± 13.3 years; males = 48%) with hemispheric ischemic stroke who underwent acute dynamic computed tomography angiography were included in the study. Overall, 56 (48%) demonstrated delayed-late venous phase cortical vein filling. Poor collateralization (OR = 13.50; 95% CI = (4.2, 43); p ≤ 0.0001) and longer time to peak of maximum arterial enhancement (OR = 3.2; 95% CI = (1.96, 5.3); p ≤ 0.0001) were positively associated with delayed-late venous phase cortical vein filling. Delayed-late venous phase cortical vein filling was independently associated with poor baseline collateral status (75% vs. 15%, p ≤ 0.0001; OR = 14.38; 95% CI = (4.33, 47.8); p ≤ 0.0001). Delayed-late venous phase cortical vein filling is frequently seen in patients with acute ischemic stroke and is associated with poor baseline collateralization.